Produksi Minyak Bunga Kenanga sebagai Upaya Penguatan Ekonomi Masyarakat - Fatimah Az Zahirah; Muhammad Dayat; Sukamto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research was motivated by the untapped potential of ylang-ylang flowers as a source of community economic strengthening in Gajahrejo Village, Purwodadi District, Pasuruan Regency. Rural communities still depend on agriculture and nature-based tourism sectors which are vulnerable to seasonal changes and conservation policies. This study aims to analyze the production process of ylang-ylang flower oil and its potential in improving the village economy. The research employed a mixed methods sequential explanatory approach with a single intrinsic case study design. Data were collected through observation, interviews, documentation, and literature review. The results show that ylang-ylang oil production has considerable economic potential because the oil has high market value and can be developed into aromatherapy, cosmetic, and natural health products. The production process includes cultivation, flower harvesting, traditional distillation, and product marketing. However, business development still faces obstacles such as limited capital, distillation technology, community skills, and market access. This study implies that the development of ylang-ylang oil based on local resources can become an alternative for sustainable rural economic strengthening